ROBUST OUTPUT FEEDBACK OF MINIMUM PHASE NON LINEAR SYSTEMS - Elisante, Emrod (Tanzania Journal of Engineering and Technology, 2018)
A robust output feedback controller is synthesized for minimum phase multivariable nonlinear systems based on the differential geometry approach. Using the internal model control structure within the input-output (I/O) linearization framework, the controller is combined with a closed-loop observer to estimate transformed states in the outer-loop. It is shown that the controller-observer combination achieves robust tracking and estimation using simple tuning parameters. The effectiveness of the proposed system is illustrated by a simulation example for control of concentration in a chemical reactor.